IMPROVED EPHEMERIS OF POORLY STUDIED ECLIPSING BINARY GSC 3950-00707 = 2MASS J20355082+5242136 - Savastru, S. V.; Marsakova, V. I.; Andrych, K. D.; Dubovsky, P. (Одеські астрономічні публікації, 2017)
We made our CCD-observations of GSC 3950-00707 by using the telescope Celestron-14 of Vihorlat Observatory and Astronomical Observatory on Kolonica Saddle. The moments of minima were calculated by using the symmetrical polynomial fit. We also analyzed the observations from automated surveys ASAS-SN and found 3 mean minima by using trigonometrical polynomial fit. The analysis of our observations and data from the surveys allows to conclude that it is the W UMa-type variable and its published period value is not accurate. We analyzed the O-C curve and corrected the elements.